2012
DOI: 10.1152/jn.00925.2011
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex mechanisms regulating the occurrence of neural spikes in human muscle sympathetic nerve activity

Abstract: Salmanpour A, Shoemaker JK. Baroreflex mechanisms regulating the occurrence of neural spikes in human muscle sympathetic nerve activity. J Neurophysiol 107: 3409 -3416, 2012. First published March 21, 2012 doi:10.1152/jn.00925.2011.-This study tested the hypothesis that the discharge patterns of action potentials (APs) within bursts of postganglionic muscle sympathetic nerve activity (MSNA) are subject to arterial baroreflex control but in a manner that varies inversely with AP size. MSNA data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
39
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
13
39
1
Order By: Relevance
“…Therefore, both a greater frequency of integrated bursts and an increased AP content within each burst, contribute to the heightened baseline sympathetic outflow in CHF. Previous observations that the high-probability APs in sinus rhythm bursts of healthy individuals are related strongly to a baroreflex mechanism (27) supports the conjecture outlined above that lower diastolic blood pressure during the sinus rhythm may contribute to the larger number of APs per burst and active clusters in CHF patients than in controls. Inasmuch as the number of APs determine the size of an integrated burst and different central mechanisms are proposed to affect burst frequency (gating) vs. size (15), these data indicate that CHF produces aberrations in both features of control, such that more efferent APs/burst and bursts/min are emitted.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, both a greater frequency of integrated bursts and an increased AP content within each burst, contribute to the heightened baseline sympathetic outflow in CHF. Previous observations that the high-probability APs in sinus rhythm bursts of healthy individuals are related strongly to a baroreflex mechanism (27) supports the conjecture outlined above that lower diastolic blood pressure during the sinus rhythm may contribute to the larger number of APs per burst and active clusters in CHF patients than in controls. Inasmuch as the number of APs determine the size of an integrated burst and different central mechanisms are proposed to affect burst frequency (gating) vs. size (15), these data indicate that CHF produces aberrations in both features of control, such that more efferent APs/burst and bursts/min are emitted.…”
Section: Discussionsupporting
confidence: 64%
“…[6, 10] The methodology counts the number of single fiber discharges (spikes) in MSNA raw signals independently of synchronized burst activity. The methodology was shown to reliably detect changes in sympathetic activity elicited by baroreflex and chemoreflex mechanisms [4, 25] or diseases, such as heart failure[34]. In the present study, we observed no consistent reduction in wavelet-based MSNA measurements following catheter-based renal nerve ablation.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, normalizing the burst size in the integrated neurogram overcomes this problem to some extent (Sverrisdóttir et al 1998) and when this is done, the distribu-tion of burst size exhibits strong within-individual reproducibility in studies separated by about 4 weeks (Kimmerly et al 2004). As an aside, baroreflex mechanisms appear to apply to the appearance of small APs only, but not the larger AP clusters (Salmanpour and Shoemaker 2012), providing a mechanistic link between earlier conjecture that larger bursts are regulated by different central features (Kienbaum et al 2001;Malpas and Ninomiya 1992).…”
Section: Microneurographic Data To Interpret Neurovascular Couplingmentioning
confidence: 88%